Levels of Support for People with Intellectual and Developmental Disabilities in Light of the Gender, Age, and Degree of Disability - Atawi , Rowaida (Dirasat: Educational Sciences, 2021)
The current study aims at identifying support levels for an individual with intellectual and developmental disabilities in the light of their age and degree of disability variables. The sample of the study encompassed (40) individuals with intellectual and developmental disabilities aged (5-16 years) who are enrolled in special education centers. The participants in the sample were chosen randomly and divided into age groups (5-8, 9-12, 13-16) and their degrees of disabilities whose cases were classified into (simple, moderate, severe). To achieve the objectives of the study, the researcher used Supports Intensity Scale™ (SIS) for intellectual and developmental disability to measure the diagnosis of support needs developed (Al-A’tawi, 2012). The results indicated that the support levels were within the pervasive support levels. Results indicated that there are statistically significant differences at the significance level (α ≥0.05) of the support levels according to the gender variable on the activities: daily life activities, community activities, vocational activities, health and safety activities, and the presence of statistically significant differences at (α ≥0.05) of support levels depending on the age group variable on activities: daily life activities, community, social, academic and professional activities. Additionally, the results of the study stated that there are statistically significant differences at (α ≥0.05) of support levels according to the degree of disability variable in all activities: daily life activities, community, social, academic, and vocational as well as health and safety activities and elf-protection activities).